Homologous Recombination Deficiency Associated With Response to Poly (ADP-ribose) Polymerase Inhibitors in Ovarian Cancer Patients: The First Real-World Evidence From China - Ni, Jing; Guo, Wenwen; Zhao, Qian; Cheng, Xianzhong; Xu, Xia; Zhou, Rui; Gu, Hongyuan; Chen, Chen; Chen, Xiaoxiang (Frontiers in Oncology, 2022)
Homologous recombination deficiency (HRD) is an approved predictive biomarker for Poly (ADP-ribose) polymerase inhibitors (PARPi) in ovarian cancer. However, the proportion of HRD positive in real world and relationship of HRD status with PARPi in Chinese ovarian cancer patients remains unknown. A total of 67 ovarian cancer patients underwent PARPi, both Olaparib and Niraparib, were enrolled and passed inclusion criteria from August 2018 to January 2021 in the Affiliated Cancer Hospital of Nanjing Medical University. Progression-free survival (PFS) was analyzed with a log-rank test using HRD status and summarized. Univariate and multiple cox-regression analysis were conducted to investigate all possible clinical factors. 68.7% (46/67) patients were HRD positive and the rest 31.3% (21/67) were HRD negative. The PFS among HRD positive patients was significantly longer than those HRD negative patients (medium PFS 9.4 m vs 4.1 m, hazard ratio [HR]: 0.52, 95% CI: [0.38-0.71], p<0.001). Univariate cox-regression found that HRD status, previous treatment lines, Eastern Cooperative Oncology Group (ECOG) status were significantly associated with PFS after PARPi treatment. After multiple regression correction, only HRD status was the independent factor to predict PFS (HR: 0.69, 95% CI: [0.51-0.93], p=0.017). In both frontline treatment and posterior line therapy group and especially in ECOG PS=0 subgroup, PFS in HRD positive patients was more significant higher than HRD negative patients . This is the first real-world data of HRD status in ovarian cancer patients from China and demonstrate that HRD is a predictive biomarker for PARP inhibitors treatment in Chinese ovarian cancer patients.